MENUJU ASEAN BEBAS NARKOBA 2015: SITUASI PENYALAHGUNAAN NARKOBA DI INDONESIA - Kartaatmaja, A.M. (Jurnal Aspirasi, 2014)
Illegal drugs cultivation, production, trafficking, and abuse are recognized as criminal acts. The number of drugs abusers in Indonesia is the highest among Southeast Asian countries. ASEAN leaders have declared to make the region a drug-free zone by 2015. This paper is conducted through literature study to examine the phenomenon of the spread of drugs in the ASEAN region. From the literature study it appears that the region is vulnerable to trans-national crime, including drug smuggling. The Indonesian people should be aware on transnational crimes as possible side effects of market liberalization. Family and local communities are the major foundation in fighting against drugs abuse. Illegal drugs distribution should be controlled by reducing both supply and demand.